How much drug allergies affect quality of life? - Gurlek, Feridun; Tasdemir, Eyyup (International Journal of Research in Medical Sciences, 2020)
Background: Drug hypersensitivity reactions are considered public health problems due to associated morbidity and socioeconomic costs. The evaluation of health-related quality of life in patients with drug hypersensitivity is still a widely unconsidered topic. The aim of our study is to reveal the effects of drug allergy on the quality of life of patients who apply to our outpatient clinic with the complaint of drug allergy. Methods: This study is prospective a questionnaire study under supervision. Patients who applied to the University of Health Sciences, Bursa Postgraduate Research and Training Hospital Department of Allergy outpatient clinic between August 2019 and May 2020 with the complaint of drug allergy filled out the quality of life questionnaire (DrHy-Q), and short questionnaire of psychological well-being index (PGWBIs) under the supervision of a specialist physician before the diagnostic procedures. Results: The study was conducted with 150 cases and 73.3 % (n=110) of the cases were female and 26.7% (n=40) were male. No significant correlation was found between the demographic characteristics of the patients, the observed symptoms, the culprit drugs, familial and individual comorbid and psychological diseases, and DrHY-Q (p>0.05). DrHY-Q was only affected from the type of allergic reaction. A negative statistically significant weak correlation was also detected between the total DrHY-Q score and the PGWBI total score (r: -0.283; p<0.01). Conclusions: We found that DrHY-Q is sensitive to reaction type and able to discriminative type 1 and type 2 reactions (p=0.017; p<0.05). We think that more comprehensive studies are needed on this subject.